1999
DOI: 10.1111/j.1469-445x.1999.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Anion efflux from cytotrophoblast cells derived from normal term human placenta is stimulated by hyposmotic challenge and extracellular A23187 but not by membrane‐soluble cAMP

Abstract: The regulation of placental anion transport influences fetal accretion and placental homeostasis. We investigated whether efflux of lZ5I-or 36Cl-from multinucleated cytotrophoblast cells derived from human term placenta is regulated by one of three stimuli: (a) the calcium ionophore A23 187, (b) a 'cocktail' of agents designed to raise intracellular levels of CAMP, (c) a hyposmotic solution. After loading with the appropriate isotope for 2 h and thorough washing, cells were exposed to sequential aliquots of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Pendrin acts as a sodium-independent transporter of chloride and iodide (12,15,25). Its location in the syncytiotrophoblast cells is compatible with several observations demonstrating that these cells control anion efflux, particularly I Ϫ and Cl Ϫ (26). The increase in PDS gene expression during gestation is in agreement with a marked maternal to fetal gradient of iodide through the villous syncytiotrophoblast layer during the second and third trimesters (1,2).…”
Section: Discussionsupporting
confidence: 81%
“…Pendrin acts as a sodium-independent transporter of chloride and iodide (12,15,25). Its location in the syncytiotrophoblast cells is compatible with several observations demonstrating that these cells control anion efflux, particularly I Ϫ and Cl Ϫ (26). The increase in PDS gene expression during gestation is in agreement with a marked maternal to fetal gradient of iodide through the villous syncytiotrophoblast layer during the second and third trimesters (1,2).…”
Section: Discussionsupporting
confidence: 81%
“…For example, placental trophoblast cells express Ca 2ϩ -activated Cl Ϫ channels (27,59), and Cl Ϫ efflux could accompany K ϩ loss following purinergic receptor activation; this would also be expected to result in cell shrinkage. A role for ATP and UTP (via P2X and P2Y receptors) in modifying Cl Ϫ secretion has been shown in various epithelial cell types (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…However, efflux experiments under parallel conditions showed that substantial 86 Rb efflux, inhibited by charybdotoxin, still occurred. One possible explanation of this paradox arises from the fact that the EC 50 for Ca 2ϩ activation of IK is very low [95-320 nM (21, 24)]. Both studies proposed that activity of this channel would be expected to occur in unstimulated cells, and thus even a marginal increase in [Ca 2ϩ ] i , which might be barely detectable, may be sufficient to activate such an efflux pathway.…”
Section: Rb Efflux Pathway In Cytotrophoblast Cellsmentioning
confidence: 99%
“…A Ca 2ϩ -activated Cl Ϫ current and a volume-activated Cl Ϫ current were also identified in these cells (28), as well as a volume-stimulated Ca 2ϩ -activated Cl Ϫ efflux pathway (50). Regulation of cation conductances is less well defined.…”
mentioning
confidence: 99%